LEADERSHIP TRAITS OF SULEIMAN THE MAGNIFICIANT, IN TERMS OF “GREAT MAN” THEORY - Rüzgar, Nilüfer (My University, 2019)
Leadership theories has been widely researched throughout the history by researchers, scholars and authors. Great Man Theory, is accepted as the first product of these researches. According to the theory, great leaders are born, not created. They hold specific and distinctive characteristics/traits of leadership innately. In this sense, among the mighty figures in world history, the 10th emperor of the Ottoman Empire, Suleiman the Magnificient (Kanuni Sultan Süleyman/Muhteşem Süleyman), is one of these figures who is accepted as a Great Man. From this point of view, the aim of this study is to examine the leadership traits of Suleiman the Magnificient, in terms of Great Man Theory, by scrutinizing the literature about leadership and scholarly works of glorious Ottoman history.

Liderlik teorileri tarih boyunca araştırmacılar, sosyal bilimciler ve yazarlar tarafından detaylıca araştırılmıştır. Büyük Adam Teorisi, bu araştırmaların ilk ürünlerinden biri olarak kabul edilmektedir. Teoriye göre lider olarak doğulur, sonradan lider olunmaz. Büyük adamlar, liderliğin ayırt edici özelliklerine doğuştan sahiptirler. Bu bağlamda, dünya tarihinin en güçlü figürleri arasında yer alan 10. Osmanlı Padişahı Kanuni Sultan Süleyman (Muhteşem Süleyman), “Büyük Adam” olarak kabul edilmektedir. Bu bakış açısından yola çıkarak hazırlanan bu çalışmanın amacı, Kanuni Sultan Süleyman’ın liderlik özelliklerini Büyük Adam Teorisi bağlamında, liderlik literatürünü ve muhteşem Osmanlı tarihi hakkındaki çalışmaları derinlemesine araştırarak, incelemektir.
Kanuni Sultan Süleyman’ın “Büyük Adam” Teorisi Bağlamında Sahip Olduğu Liderlik Özellikleri
Keywords: [No Keywords]